Fatores socioambientais determinantes de parasitoses intestinais na localidade Homero Figueiredo, Feira de Santana, Bahia, Brasil – Ba - Oliveira, Alany Santos (2009)
The intestinal parasites are diseases whose etiologic agents are helminth or protozoa, which are present in endemic form in different areas of Brazil, being a major public health problems due to the difficult accession to basic sanitation and education for the poor population, since the transmission of these agents is directly related to living conditions and hygiene of the population. This work was in object to identify the determining factors social environment in the spread of helminth and protozoa among people of the town Homero Figueiredo, Feira de Santana - BA, which has local supply of sanitation. For this, individual and relatives forms have been applied to verify the epidemiological aspects of population under study. Furthermore, it enhances the parasitological feces of the population, to search for helminth and protozoa. From the results obtained in the survey and parasitologic analysis, we found that were positive for intestinal parasites, despite the presence of minimum conditions of sanitation and water supply and sewage collect and treatment, and that some habits can mean at risk of contamination by parasites. Faced with this, it is concluded that the rate of intestinal parasites and commensals, in a locality, is associated with cultural factors, economic and environmental conditions in the local housing and social living. It is important to consider that, besides improving socio-economic conditions and infrastructure is needed, also the engagement, which is one of the key considerations for deployment, development and success of control programs.